Management of foreign object in the root canal of central incisor tooth - Mothanna Alrahabi; Hani Gabban (Wolters Kluwer Medknow Publications, 2014)
There are several reports describing the impaction of foreign objects into the exposed pulp chambers and canals by patients, especially children as they often have the habit of inserting foreign objects in the oral cavity. These objects will become a potent source of infection.This case report describes the retrieval of a foreign object impacted into the root canal of a 12-year-old male patient who was referred to the endodontic specialty clinic at Taibah University College of Dentistry. The patient's chief complaint was a pain in the upper left central tooth. Clinical examination revealed a complicated enamel-dentin fracture with a large caries cavity. A periapical radiographic image showed a radiopaque object in the root canal system. Stainless steel Hedstrom files were used to retrieve the object from the canal. Following a proper cleaning and shaping of the root canal system, an intra-canal calcium hydroxide dressing was placed for 1 week. The root canal system was then filled with sealer and gutta-percha using the lateral compaction technique and the tooth received an aesthetic restoration.